Restoring soil carbon in marginal land of Indian Himalayas: Impact of crop intensification and conservation tillage. (15th September 2022) - Das, Anup; Babu, Subhash; Datta, M.; Kumar, Sanjeev; Singh, Raghavendra; Avasthe, Ravikant; Rathore, S.S.; Yadav, S.K.; Singh, Vinod K.
Abstract: Soil carbon (C) loss is the prime sign of land degradation, and C pools have a great impact on soil quality and climate change mitigation. Hence, a field experiment was conducted for three consecutive years to assess the impact of crop intensification and conservation tillage practices on changes in the C pool at different soil depths of marginal land of the Indian Himalayas. The experiment consisted of two intensified cropping systems viz., CS1-Summer maize ( Zea mays L.) –rainy season maize–lentil ( Lens esculenta L.) and CS2-Summer maize–rainy season maize–mustard ( Brassica juncea (L.) Czern) and five tillage practices viz., No-till (NT); NT + live mulch of cowpea (NT + LMC); reduced tillage (RT); RT + LMC and conventional tillage (CT). Results revealed that CS2 produced significantly higher biomass, C retention efficiency (9.85%), and sequestrated greater C (0.42 Mg ha −1 yr −1 ) in the soil system than CS1. Of the various tillage practices, RT + LMC registered higher biomass and recycled greater biomass and C than those under other tillage practices. However, the highest soil organic carbon (SOC) content (7.03 g kg −1 ) and pool (9.62 Mg ha −1 ) in 0–10 cm depth were observed under NT + LMC. The non-labile C pool size under NT in 0–10 cm and 10–20 cm depths was significantly greater than those under CT. The NT + LMC sequestrated significantly higher SOC (0.57 Mg ha −1 yr −1 ) than other tillage practices. Thus, the study indicated that the adoption of an intensified maize-based system under RT + LMC or NT + LMC would increase SOC storage and C sequestration in marginal lands of the Indian Himalayas. Highlights: Cowpea live mulch (LMC) based conservation tillage enhanced total C production. Reduced tillage (RT)+ LMC recycled greater biomass and C than NT + LMC system. No-till (NT) +LMC had the highest SOC pool (9.62 Mg ha −1 ) in 0–10 cm depth. NT/RT + LMC achieved 10.16–17.39‰ C storage per year.